Politics, Hollywood style : American politics in film from Mr. Smith to Selma - Heyrman, John, 1960- (Politics, literature, & film., 2018)
"This book analyzes major films about the American political process since the 1930s. It considers the films' major themes about politics, ideology, and representation of race and gender over the past several decades"--